SCIENTIFIC BASED SPARKOL VIDEOSCRIBE MEDIA: MATHEMATICS LEARNING MEDIA INNOVATION DURING THE PANDEMIC COVID 19 - Iik Nurhikmayati; Nia Kania (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
The spread of the coronavirus has made the entire educational system shift to online learning. The key challenges are the uneven distribution of the internet network and the expensive use of quotas. Creating learning material allows students to study from home without relying on the internet or massive quotas. One of the best learning options during this pandemic is developing sparkol video scribe-based learning material. During the Covid 19 pandemic, this study intends to build scientifically based sparkol video scribe media and describe the quality of scientifically based sparkol video scribe media in mathematics learning in terms of validity, practicality, and effectiveness. The research approach is Research and Development (R&D), which follows the ADDIE framework, consisting of five steps: planning (design), development, implementation, and evaluation. The research subjects were 15 students from the fourth semester of Universitas Majalengka's mathematics education studies program. Validation test sheets, practicality sheets, and effectiveness sheets were among the instruments employed. The findings revealed that developed media met the standards established by media and material experts, were used in classrooms, and effecinfluentialhanced student interest in learning and arithmetic skills. During the Covid 19 epidemic, the sparkol video scribe media deserves to be employed as an alternative learning medium.Dampak penyebaran virus corona membuat seluruh sistem pendidikan telah beralih ke pembelajaran online. Tantangan utamanya adalah distribusi jaringan internet yang tidak merata dan penggunaan kuota yang mahal. Menciptakan materi pembelajaran yang memungkinkan siswa untuk belajar dari rumah tanpa bergantung pada internet atau kuota yang besar sangatlah penting. Salah satu pilihan pembelajaran terbaik di masa pandemi ini adalah pengembangan materi pembelajaran berbasis sparkol video scribe. Di masa pandemi Covid 19, penelitian ini bermaksud untuk membangun media video scriber sparkol berbasis ilmiah dan mendeskripsikan kualitas media video scribe sparkol berbasis ilmiah dalam pembelajaran matematika ditinjau dari validitas, kepraktisan, dan keefektifannya. Pendekatan penelitian adalah Research and Development (R&D), yang mengikuti kerangka ADDIE, terdiri dari lima langkah: perencanaan (design), pengembangan, implementasi, dan evaluasi. Subjek penelitian adalah 15 mahasiswa semester IV program studi pendidikan matematika Universitas Majalengka. Lembar uji validasi, lembar kepraktisan, dan lembar keefektifan termasuk di antara instrumen yang digunakan. Temuan menunjukkan bahwa media yang dikembangkan memenuhi standar yang ditetapkan oleh ahli media dan materi, digunakan di dalam kelas, dan efektif  dalam meningkatkan minat siswa dalam belajar dan keterampilan berhitung. Di masa mewabahnya Covid 19, media video scribe sparkol layak dijadikan sebagai media pembelajaran alternatif